2018
DOI: 10.1007/s00268-018-4569-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Total Body Prehabilitation on Post‐Operative Outcomes After Major Abdominal Surgery: A Systematic Review

Abstract: There is substantial heterogeneity in the prehabilitation programmes used prior to major abdominal surgery. A multimodal approach is likely to have better impact on functional outcomes compared to single modality; however, there is insufficient data either to identify the optimum programme, or to recommend routine clinical implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 51 publications
1
66
0
Order By: Relevance
“…Review articles have found conflicting results on these programs, mainly due to the heterogeneity of the studies and focus on single risk-factors in the included studies. [258][259][260] At least, the idea of "prehab" does not seem to have any negative outcomes, and international randomised trials are ongoing. 261 Although promising evolvements have been made, the level of postoperative complications in the SCRCR has remained rather stable for the last two decades.…”
Section: Post-operative Complicationsmentioning
confidence: 99%
“…Review articles have found conflicting results on these programs, mainly due to the heterogeneity of the studies and focus on single risk-factors in the included studies. [258][259][260] At least, the idea of "prehab" does not seem to have any negative outcomes, and international randomised trials are ongoing. 261 Although promising evolvements have been made, the level of postoperative complications in the SCRCR has remained rather stable for the last two decades.…”
Section: Post-operative Complicationsmentioning
confidence: 99%
“…A burgeoning body of research is investigating the utility of preoperative interventions, known as prehabilitation, to optimize posttreatment health outcomes. Numerous reviews of the prehabilitation literature in cancer populations demonstrate several important benefits, including improved preoperative and postoperative physical function, reduced hospital length of stay, and fewer postoperative complications (18)(19)(20)(21)(22)(23)(24). However, this literature exists almost exclusively in people undergoing tumor resection for thoracoabdominal malignancies, with breast cancer prehabilitation remaining largely unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…The major interest on this topic of high clinical importance is clearly illustrated by seven very recent systematic reviews and meta-analyses [22,[27][28][29][30][31][32]. Summarizing these results there is significant heterogeneity between studies.…”
Section: Prehabilitationmentioning
confidence: 99%